Color-taste correspondence tested by the Stroop task - Yang, Yidie; Chen, Na; Kobayashi, Maiko; Watanabe, Katsumi (Frontiers in Psychology, 2024)
People consistently associate colors with tastes (e.g., pink-sweet, yellow-sour). However, little has been known on the strength of those color-taste correspondences. The current study examined the congruency effect of color-taste correspondence using two Stroop word categorization tasks. The visual stimuli consisted of food names associated with sweet and sour tastes, presented in different shades of pink and yellow font colors. Participants were instructed to categorize the taste (sweet or sour) of the words in the Stroop word-taste categorization task and to discriminate the font color (pink or yellow) of the words in the Stroop word-color discrimination task. Results showed that participants responded faster in congruent conditions (sweet-pink and sour-yellow) than incongruent conditions (sweet-yellow and sour-pink) in both tasks. Specifically, yellow font colors facilitated the categorization of sour taste words compared to pink font colors, whereas sweet taste words facilitated the discrimination of pink font colors compared to sour taste words. These results provide further evidence for the congruency effect of color-taste correspondence in facilitating the processing of tasterelated words and colors. Furthermore, the congruency effect was shown to operate bidirectionally, influencing both the conceptual meaning of tastes and perceptual color perception. This study highlights the significant interference effect of color-taste correspondence on cognitive processing as assessed by the Stroop task.